The influence of diet on recovery from prolonged exercise - Amanda J. Patton (1985)
Endurance capacity has been shown to be related to the magnitude of pre-exercise muscle glycogen stores (Bergstrom, Hermansen, Hultman and Saltin 1967) and, moreover, fatigue during prolonged exercise is associated with a depletion of these stores (Saltin and Hermansen 1967). The rate of repletion of muscle glycogen and, therefore, recovery from prolonged exercise is most rapid when a high carbohydrate (CHO) diet is consumed (Costill and Miller 1980). The purpose of this study was to investigate the effect of a high CHO diet on recovery from exhaustive exercise using a performance test to assess the efficacy of such a diet. The CHO content of the diet was increased by supplementation of the normal diet with confectionery products. Confectionery products were used as these provide CHO in an "easy to eat" form when it is not possible to consume the more conventional high CHO foods. [Continues.]